ERA DISRUPSI TEKNOLOGI 4.0 DAN ASPEK HUKUM PERLINDUNGAN DATA HAK PRIBADI - sri ayu astuti (Universitas Pakuan, 2020)
ABSTRACTThe stopping of the Covid Pandemic -19 gives the effect of changes in social interaction in life in the community especially when it is disrupted which has controlled human life sociologically and psychologically in every movement in life, especially since the existence of a pandemic there has been a change in work culture that was originally in the conventional form of switching to online space because of the policy of doing work by way of WFH work from home. Technological advances in the era of the utilization of technology 4.0 have become evident in their use, not even in their total mastery of internet applications, the interaction of everyone in Indonesia, including ethical behavior in communication in the technology space, eventually leading to legal problems that intersect with law enforcement of ITE Law Number 19 of 2016 against function of its use. every person who is in the vortex of using technological advances must be confronted with no maximum legal efforts to do legal protection of personal rights including personal data that is so easily accessed by implementing an internet-based technology system. This is the responsibility of the state, namely the organizer of the Government of the Republic of Indonesia in the jurisdiction of Indonesia, which grants permission to operate as an owner and manager of a technological system that carries out its operations in the sovereignty of a State, which can impose strict sanctions on the legal remedies for protecting every citizen from criminal acts of moving virtual.Keywords: Disruption Era, Technological Uses, Personal data protection ABSTRAK Hentakan adanya Pandemi Covid -19 memberikan pengaruh terjadinya perubahan interaksi sosial dalam kehidupan dalam masyarakat terlebih diera disrupsi yang telah menguasai hidup manusia secara sosiologis dan psykologis disetiap gerak dalam kehidupan, apalagi sejak adanya pandemi terjadi perubahan budaya kerja yang semula dalam bentuk konvensional beralih ke ruang online karena adanya kebijakan melakukan pekerjaan dengan cara WFH work from home. Kemajuan teknologi dalam era kemanfaatan teknologi 4.0 menjadi nyata penggunaannya, bahkan belum secara total penguasaannya pada aplikasi internet, interaksi setiap orang di Indonesia termasuk perilaku etika dalam komunikasi di ruang teknologi hingga akhirnya menimbulkan permasalahan hukum yang bersinggungan dengan penegakkan hukum UU ITE Nomor 19 Tahun 2016 terhadap fungsi penggunaannya. setiap orang yang berada dalam pusaran penggunaan kemajuan teknologi harus dihadapkan tidak maksimalnya upaya hukum dilakukannya perlindungan hukum hak pribadi termasuk data-data pribadi yang begitu mudah diakses dengan penerapan sistem teknologi berbasis internet. Hal ini menjadi tanggungjawab negara yakni penyelenggara Pemerintah Republik Indonesia di wilayah hukum Indonesia yang memberikan ijin beroperasinya pemilik sekaligus pengelola sistem teknologi yang melakukan operasionalnya dalam kedaulatan suatu Negara, yang dapat memberikan sanksi tegas terhadap upaya hukum perlindungan setiap warga negara atas tindak pidana kejahatan yang bergerak secara virtual.Kata Kunci : Era Disrupsi, Kemanfaatan Teknologi, Perlindungan data pribadi